2021
DOI: 10.4102/sajcd.v68i1.741
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of newborn hearing screening at an academic secondary level hospital in Johannesburg, South Africa

Abstract: Background The Health Professions Council of South Africa (HPCSA) issued early hearing detection and intervention guidelines, which has universal newborn hearing screening (UNHS) as one of the important goals. Despite established evidence of the importance of UNHS globally, there has been no mandated formalised and standardised implementation as yet in South Africa. Objectives The aim of this study was to describe the outcomes of newborn hearing screening (NHS) in an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Current studies and guidelines recommend de-specialisation of hearing screening services to other personnel who will be trained and will have to adhere to regulated standards (Khoza-Shangase et al, 2017 ; Khoza-Shangase & Kanji, 2021 ). Equipment that is easy to use and sensitive, creates opportunities to use non-professionals as screeners, to reach contexts where audiologists are not available (Bezuidenhout, Khoza-Shangase, De Maayer, & Strehlau, 2021 ; Khoza-Shangase & Kanji, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies and guidelines recommend de-specialisation of hearing screening services to other personnel who will be trained and will have to adhere to regulated standards (Khoza-Shangase et al, 2017 ; Khoza-Shangase & Kanji, 2021 ). Equipment that is easy to use and sensitive, creates opportunities to use non-professionals as screeners, to reach contexts where audiologists are not available (Bezuidenhout, Khoza-Shangase, De Maayer, & Strehlau, 2021 ; Khoza-Shangase & Kanji, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore important to gather information about parental or caregiver perspectives on NHS to ensure appropriate advocacy and interventions (Jatto, Ogunkeyede, Adeyemo, Adeagbo, & Saiki, 2018 ). Furthermore, NHS programmes are not mandatory in South Africa (Bezuidenhout et al, 2021 ), thus necessitating parents being aware and knowledgeable of the risk factors for infant hearing loss (Govender & Khan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful and comprehensive hearing function monitoring protocols need to be implemented to ensure a more accurate description and categorization of the type, degree, onset and development of the hearing loss, as well as the influencing factors-as explored in the current study. South African researchers argue for such protocols within the South African context as preventive measures where contextual challenges require them [25][26][27][28]. Secondly, the fact that some of the participants presented with conductive or mixed hearing loss (30.6%); which is reversible in nature, highlights the importance of multidisciplinary team work where otorhinolaryngologists could form part of the team to ensure that the middle ear pathology is treated so that it does not progress and cause more permanent damage.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies indicated rescreening, and increasing age at initial screening has reduced the refer rate as well as high false positive rate [16][17][18][19][20][21][22][23]. e overall refer rates of NHS programs in developing and developed countries vary considerably.…”
Section: Introductionmentioning
confidence: 99%